Precision caffeine therapy for apnea of prematurity and circadian rhythms: New possibilities open up - Dai, Hao-Ran; Guo, Hong-Li; Hu, Ya-Hui; Xu, Jing; Ding, Xuan-Sheng; Cheng, Rui; Chen, Feng (Frontiers in Pharmacology, 2022)
Caffeine is the globally consumed psychoactive substance and the drug of choice for the treatment of apnea of prematurity (AOP), but its therapeutic effects are highly variable among preterm infants. Many of the molecular underpinnings of the marked individual response have remained elusive yet. Interestingly, the significant association between Clock gene polymorphisms and the response to caffeine therapy offers an opportunity to advance our understanding of potential mechanistic pathways. In this review, we delineate the functions and mechanisms of human circadian rhythms. An up-to-date advance of the formation and ontogeny of human circadian rhythms during the perinatal period are concisely discussed. Specially, we summarize and discuss the characteristics of circadian rhythms in preterm infants. Second, we discuss the role of caffeine consumption on the circadian rhythms in animal models, humans, especially in neonates and preterm infants. Finally, we postulate how circadian-based therapeutic initiatives could open new possibilities to promote precision caffeine therapy for the AOP management in preterm infants.